Public health 101 : improving community health - Riegelman, Richard K.; Kirkwood, Brenda (Burlington, Massachusetts : Jones & Bartlett Learning, 2025)
"Public Health 101: Improving Community Health introduces undergraduate students to not only the profession of public health, but the ways of thinking encompassed by population health. Population health prepares students for the challenges in our society related to public health, helping frame the issues and analyze options to intervene. Population health requires an evidence-based approach to collecting and using facts to develop and implement approaches to improve community health. This text utilizes a unique approach to introducing students to key concepts, and students come away with a clear understanding of how public health affects their everyday lives"--
"From clean drinking water, to seat belts, to immunizations, the impact of public health on every individual is undeniable. For undergraduates, an understanding of the foundations of public health is an essential step toward becoming an educated citizen. Public Health 101: Improving Community Health, Fourth Edition by Riegelman and Kirkwood provides a big-picture, population perspective on the determinants of health and disease and the tools available to protect and promote health. Now with a greater emphasis on community involvement and providing community based-services, the fourth edition examines the full range of options for intervention including use of the healthcare system, the public health system, and society-wide systems such as laws and taxation.Through a unique set of case studies, vignettes, and extensive examples, readers will come away with a clear understanding of how public health affects their everyday lives. They will learn and apply frameworks for thinking about public health issues and gain a deeper understanding about the health news they are exposed to each day.Updated throughout, Public Health 101, Fourth Edition offers: New case studies on folic acid and spina bifida, the opioid epidemic, athletic health injuries, mPox, and the patient safety movement. Interactive COVID-19 case studies revised and consolidated to take an historical perspective on the COVID-19 pandemic. Updated materials for each chapter including Healthy People 2030, pandemic prevention, new vaccines, environmental justice and climate change, and academic health departments. New Boxes in each chapter including misinformation/disinformation, suicide, health advocacy, national dietary guidelines, and open notes. Improving Population Health interactive exercises and interactive lectures retained from 3rd edition Updated faculty resources, including Instructor's Manual with sample answers to most case studies, test bank, sample examinations, sample syllabus, PowerPoint slides, and videos with annotations for each chapter. Navigate Advantage Access that unlocks a comprehensive and interactive eBook, student practice activities and assessments, a full suite of instructor resources, and learning analytics reporting tools"--
Previous edition: 2019
Includes bibliographical references and index
Keywords: Public health -- Textbooks; Public Health